Synovial Cysts of the Temporomandibular Joint: An Immunohistochemical Characterization and Literature Review. (20th March 2013) - Vera-Sirera, B.; Tomás-Amerigo, J. A.; Baquero, C.; Vera-Sempere, F. J.
Abstract : Synovial cysts of the temporomandibular joint (TMJ) are very rare, and to date, only 12 cases of a synovial cyst in the TMJ region have been reported in the literature. In this paper, we present the clinicopathological and immunohistochemical characteristics of one such lesion affecting a 48-year-old woman, presented with a mass in the left preauricular region. We describe the usefulness of immunohistochemical analysis for recognizing the synovial lining, which allowed for clear differentiation between ganglion and synovial cysts. Immunohistochemical analyses can be used to diagnose synovial cysts with certainty; however, using at least two markers is advisable to distinguish the two existing synovial cell subtypes. Our findings indicate that synovial cysts of TMJ possess an internal lining dominated by type B (fibroblast-like) synoviocytes.